Molecular characterisation, biology, behaviour and feeding potential of a novelpredator of the mango ecosystem: Sycanus bifidus (Fabricius, 1787) - Bhagyasree, S N; Baradevanal, Gundappa; Kumari, Nidhi (Journal of Horticultural Sciences, 2025)
This study provides an overview of the comprehensive study on Sycanus bifidus, a new generalist predatory fauna collected from mango ecosystem, encompassing its molecular characterization, biology, behaviour and feeding potential. The research delves into the intricate details of S. bifidus, shedding light on its morphological features, and ecological significance. Molecular characterization techniques, including DNA sequencing and genetic analysis, play a pivotal role in elucidating the species genetic makeup, population dynamics, and potential adaptations. The study also explores the intricate biology and behaviour of S. bifidus. Furthermore, the research investigates the feeding potential of S. bifidus, emphasizing its role as a predator in controlling pest populations. An in-depth analysis of its feeding habits, and efficiency as a biological control agent provides valuable information for the development of sustainable pest management strategies.
Keywords: Feeding potential; mango; molecular characterization; predatory efficiency; Sycanus bifidus